두개강내 출혈로 진단된 전이성 융모막암종 증례보고 - 이영진; Young Jin Lee; 김아리; Ari Kim; 조해중; Hae Joong Cho; 박성남; Seong Nam Park; 홍성남; Sung Nam Hong; 김흥열; Heung Yeol Kim (Obstetrics & gynecology science, 2012)
융모막암종은 임신성 융모상피암에서 가장 악성의 형태를 띠는 암종이며, 빠른 시일에 자라 폐, 간, 그리고 드물긴 하지만 뇌로 전이된다. 이 암종은 포상기태임신과 관계 있으며, 다양한 장기로의 혈행성 전이, 높은 융모성선자극호르몬수치, 그리고 항암치료에 반응을 잘하는 특징이 있다. 예후는 치료가 잘되면 좋은 암종이다. 우리는 분만 후 두개강내 출혈 소견으로 내원한 36세 여성에서 개두술을 시행하였고, 병리조직검사상 융모막암종의 전이로 밝혀진 드문 예를 경험하였기에 간단한 문헌고찰과 함께 보고하는 바이다. Choriocarcinoma is the most malignant tumor of gestational trophoblastic neoplasia, which grows rapidly and metastasizes to the lung, liver, and, less frequently, brain. This tumor is known for its association with molar pregnancy, rapid hematogenous spread to multiple organs, high human chorionic gonadotropin levels, and good response to chemotherapy. Metastases to the brain are responsible for most of the deaths from choriocarcinoma. Its prognosis is generally good when treated. We report a rare case of metastatic gestational choriocarcinoma as an initial presentation of intracerebral hemorrhage.